Theater documentation: Audiovisual recording of theatrical performances - Linares Ávila, Carlos (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper analyzes the work of dissemination of the scenic heritage carried out by the Center for Research and Resources of the Performing Arts of Andalusia (CIRAE) through the video recordings available in Elektra, the Digital Archive of the Performing Arts of Andalusia. For this purpose, a sample of 84 video recordings was analyzed following a quantitative-descriptive methodology. The results of the analysis show relevant deficiencies in the archive’s videographic documentary collection. Thus, the research concludes a series of points for improvement in the work of videographic dissemination of the Andalusian performing heritage carried out by the CIRAE.